Septicemic melioidosis in a comorbid patient with familial history of tuberculosis: A case report with special reference to microbiological profile (Indian Journal of Case Reports, 2025)
Burkholderia pseudomallei is a Gram-negative, facultative intracellular bacterium commonly found in the rhizosphere of tropical soils. It causes melioidosis, a disease that spreads through skin contact, ingestion, or inhalation of contaminated soil or water. This emerging pathogen is often misdiagnosed, as it mimics various clinical conditions, including pulmonary tuberculosis, and frequently presents as community-acquired pneumonia. Key risk factors for infection include underlying conditions such as diabetes mellitus, chronic lung disease, liver and kidney disorders, alcohol abuse, chronic skin ulcers, and occupational exposure. This report discusses a case of septicemic melioidosis in a farmer with a family history of tuberculosis, who was promptly diagnosed and successfully treated with appropriate antibiotics, leading to full recovery.